A model to evaluate the environmental and energetic efficiency of the territorial functionality (transport and activity location) - Jorge Cerda; Carlos Marmolejo; Josep Roca (European Regional Science Association (ERSA), 2011)
The main objective of the study is the development of a model for the evaluation of the environmental and energy efficiency of the interaction (mobility) and land use structure (called as 'territorial functionality'), applied to the metropolitan area of Barcelona . In particular there are four points that underpin the model: a) a basic land use-transportation model (LUTM), b) a model for the energy consumption and environmental emissions produced by the territorial functionality, c) a model for the consumption of land produced by the territorial functionality (developed land), and d) assessment of social equity in access to urban activities, and exposure to environmental effects. The goodness of the proposed model is that is composed of empirical models (econometric), robust in their specific topic, but spatially disaggregated (municipality). With this structure is possible to evaluate the effects of functional changes (transport projects or urban planning) in the spatial structure of energy consumption, environmental emissions, and consumption of land, and also identifying the participation (responsibility) of different territories in these effects. It is a systemic and spatial view of the role that each territory plays in the functionality, and their responsibility in the environmental effects. The model is currently under construction, joining the calibrated models of consumption and environmental emissions to an existing transport model in the metropolitan area of Barcelona. This paper presents the mathematical model, and the indicators defined for characterizing the state of the territorial system, and a simple simulation of the possible analysis and results.
Keywords: 330